Comparative study on the potential risk of contaminated-rice straw, its derived biochar and phosphorus modified biochar as an amendment and their implication for environment. (15th January 2022) - Zong, Yutong; Chen, Han; Malik, Zaffar; Xiao, Qing; Lu, Shenggao
Abstract: Direct application of contaminated-rice straw (CRS) to soil can cause the secondary pollution in agricultural land because of high content of Cd in rice straw. This study employed biochar or modified biochar technique to reduce the potential pollution risk of Cd in CRS. In the pot experiment, the CRS, straw biochar prepared at 300 °C (B300) and 500 °C (B500), and phosphorus modified biochar pyrolyzed at 300 °C (PB300) and 500 °C (PB500) were added at dosage of 5% into three typical paddy soils. The results showed that CRS and its derived biochar could enhance soil pH, EC, Eh, organic carbon, exchangeable base cations (K +, Na +, Ca 2+ and Mg 2+ ), and available phosphate. The application of CRS, biochar and phosphorus modified biochar significantly increased the contents of total Cd in soils relative to control soil. Compared to CRS, the biochar application (especially the PB500) decreased the contents of 0.01M CaCl2 -extractable Cd. The application of CRS significantly increased the content of exchangeable Cd fraction (F1), whereas biochar increased residual Cd content (F4). The biochar and phosphorous modified biochar significantly decreased the contents of bioavailable Cd in soils compared to CRS application. The increased soil pH and dissolve organic matter were found to be the main factors in reducing the release of Cd in biochar. The possible mechanisms of biochar in reducing bioavailability of Cd were to significantly increase soil pH, enhance the complexation of Cd ions, and promote the transformation of Cd from easily available to stable (residual) forms. It could conclude that conversion of contaminated rice straw into biochar was an efficient way to minimize Cd availability in soil and reduce the pollution risk of Cd in rice straw. Graphical abstract: Image 1 Highlights: Contaminated rice straw (CRSs) and biochar application had increased total Cd. CRSs application significantly increased bioavailable Cd. CRSs converted biochar application restricted the release of bioavailable Cd to soil. Soil properties and Cd releasing rate had collectively determined Cd bioavailability.